Editorial and Production Team - Editorial Team (The Toro Historical Review, 2023)
Editors Daniella Enriquez Christopher Garcia Alexander Gonzalez Shaleyah Haywood Jason Kooken Christian Palomares Montse Romero Dr. Joshua J. Jeffers, faculty mentor